Gene replacement techniques for Escherichia coli genome modification - Madyagol, Mahesh; Al-Alami, Hend; Levarski, Zdeno; Drahovská, Hana; Turňa, Ján; Stuchlík, Stanislav (Folia microbiologica, 2011)
The subject of this review covers modern experimental procedures for chromosomal gene replacement in Escherichia coli and related bacteria, which enable the specific substitution of targeted genome sequences with copies of those carrying defined mutations. Two principal methods for gene replacement were established. The first "in-out" method is based on integration of plasmid into bacterial chromosome and subsequent resolving of the cointegrate. The "linear fragment" method (recombineering) is based on homologous recombination mediated by short homology arms at the ends of linear DNA molecule. Many new protocols and improvements in targeted gene replacement were introduced during the last 10 years. These methods are well suited for high-throughput functional gene studies and for many biotechnological applications.
Keywords: genový targeting; genetické inženýrství; Gene Targeting; Genetic Engineering; Gene Transfer Techniques; Escherichia coli; technika přenosu genů; Genome, Bacterial; Bacteriophage lambda; bakteriofág lambda; genom bakteriální